A randomized phase 3 trial to assess the immunogenicity and safety of 3 consecutively produced lots of freeze-dried MVA-BN® vaccine in healthy adults. Issue 2 (9th January 2023) - Turner Overton, Edgar; Schmidt, Darja; Vidojkovic, Sanja; Menius, Erika; Nopora, Katrin; Maclennan, Jane; Weidenthaler, Heinz
Highlights: Neutralizing antibody responses were equivalent across 3 FD MVA-BN production lots. Robust total antibody responses were also similarly observed across lot groups. Safety was comparable across lot groups and consistent with previous MVA-BN trials. Abstract: Since vaccination remains the only effective protection against orthopox virus-induced diseases such as smallpox or monkeypox, the strategic use and stockpiling of these vaccines remains of significant public health importance. The approved liquid-frozen formulation of Bavarian Nordic's Modified Vaccinia Ankara (MVA-BN) smallpox vaccine has specific cold-chain requirements, while the freeze-dried (FD) formulation of this vaccine provides more flexibility in terms of storage conditions and shelf life. In this randomized phase 3 trial, the immunogenicity and safety of 3 consecutively manufactured lots of the FD MVA-BN vaccine was evaluated. A total of 1129 healthy adults were randomized to 3 treatment groups (lots 1 to 3) and received 2 vaccinations 4 weeks apart. For both neutralizing and total antibodies, a robust increase of geometric mean titer (GMT) was observed across all lot groups 2 weeks following the second vaccination, comparable to published data. For the primary results, the ratios of the neutralizing antibody GMTs between the lot group pairs ranged from 0.936 to 1.115, with confidence ratios well within the pre-specified margin of equivalence. Results for total antibodies were similar. In addition, seroconversion rates were high across the 3 lots, ranging between 99.1 % and 99.7 %. No safety concerns were identified; particularly, no inflammatory cardiac disorders were detected. The most common local solicited adverse events (AEs) reported across lot groups were injection site pain (87.2%) and erythema (73.2%), while the most common general solicited adverse events were myalgia, fatigue, and headache in 40.6% to 45.5% of all participants, with no meaningful differences among the lot groups. No related serious AEs were reported. In conclusion, the data demonstrate consistent and robust immunogenicity and safety results with a freeze-dried formulation of MVA-BN. Clinical Trial Registry Number: NCT03699124.